GENDER MAINSTREAMING IN GOVERNANCE: MODEL AND POLICY - Intan Fitri Meutia; Mutiara Septiani Eka Putri; Pairul Syah; Yolanda Natsya (Adisam Publisher, 2026)
Gender inequality is a condition that places women after men which then raises the gender equality movement through Gender Mainstreaming (PUG). Gender mainstreaming has not been too revealing of results and enjoyed equally in Lampung Province so that a policy is needed as a real effort in implementing Gender Mainstreaming. This study aims to look at the efforts of the Lampung Province government as policy makers in realizing gender equality in Lampung Province through a qualitative approach. The results of this study indicate that Gender Mainstreaming in Lampung Province is stated in the Lampung Provincial Regulation Number 10 of 2011 concerning Gender Mainstreaming in Regional Development and is at the socialization stage as a form of strengthening the acceleration of the implementation of Gender Mainstreaming in Lampung Province.